О детонации в зоне горения растительных горючих материалов в результате внешнего воздействия - Старосельцева, Ася Алексеевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
This work is devoted to the study of the issue of extinguishing a natural fire by the impact of a shock wave on the burning zone. Based on the original methods and approaches for application of high-speed infrared thermography developed at Tomsk State University, this work presents the results of an experimental study of the shock wave effect on the flame during combustion of vegetable flammable materials. A shock tube with different nozzles and an energy source from a gunpowder charge were used to form the shock wave. The impact of the shock wave on the pyrolysis zone was recorded in the narrow band infrared wavelength range of 2.5-2.7 μm. It has been established that the impact of the shock wave on the pyrolysis zone when expanding nozzles is used results in the detonation of pyrolysis products, which leads to the cessation of flame combustion and subsequent decrease in the surface temperature of plant combustibles below the autoignition temperature. This effect leads to a break in the chain of transformation and energy release during combustion. The obtained result should be considered as a fundamental basis for the development of new effective means of fighting large natural fires based on the impact of a shock wave.